Review of Ukrainian Species of the Genus Meliboeus (Coleoptera, Buprestidae, Agrilinae) - Prokhorov, A.V. (Вестник зоологии, 2011)
Five Ukrainian species of the genus Meliboeus are reviewed and keyed and the data on their distribution in the Palaearctic Region and Ukraine, examined material and larval host plants are given. A poorly known species Meliboeus morawitzi (Semenov, 1905) is redescribed.